Garden and landscape, the spatial and the ethical: the impact of enclosure on an enclosed garden, the case of Artas, Palestine. (4th July 2017) - Egoz, Shelley; Williams, Tim
Abstract: Garden and landscape are closely associated concepts: both have concrete physical spatial characteristics yet often embody intangible symbolic and poetic dimensions. At the same time, an inherent tension exists between the two: while garden is defined by enclosure, landscapes are not marked by borders. The case of Artas, a Palestinian village that is encroached upon on both sides by external development—an Israeli settlement on the one and a Palestinian refugee camp on the other—is described in this paper through the metaphor of the enclosed garden. The disadvantaged geographic and political predicament of Artas prompts reflections on the ethical dimensions related to landscape and garden in the context of spatial infringement. The discussion is framed within a conceptual multiplicity of the term landscape, the discourse of the Right to Landscape and an exploration of the meaning of borders in terms of landscape.